Problematika Pembelajaran Ilmu Balāghah di Kelas XI Madrasah Āliyah Pondok Pesantren Modern Al-Mu’minien Lohbener Indramayu - Sani, Ana Mutiara; Yusron Hidayat; Ahwil Lutan Hidayah (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze and explain how the Balāghah Science learning system and process takes place, and what problems are faced by students in learning Balāghah Science, as well as what efforts are made to overcome the problems in learning Balāghah Science in Class XI of MA Al-Mu'minien. This study uses a qualitative approach with the type of research in the form of field research, or what is often known as